Transabdominal Laparoscopic Ureteroureterostomy With the Intraoperative Retrograde Ureteroscopy-Assisted Technique for Multiple Ureteral Polyps: A Single-Center 10 Years Experiences - Xia, Weiping; Chen, Xiang; Li, Bingsheng; Chen, Hequn; Zhu, Zewu; He, Yao; Gan, Yu; Zhang, Bo; Wang, Kangning; Li, Yang; Jiang, Zexiang; Long, Jin; et al. (Frontiers in Surgery, 2022)
Abstract Background: the purpose of this study was to report our experience in treating multiple ureteral polyps with transabdominal laparoscopic ureteroureterostomy (LAP-UU) with intraoperative retrograde ureteroscopy (RU)-assisted technique. Methods: The data of 32 patients who underwent transabdominal LAP-UU with the intraoperative retrograde ureteroscopy-assisted technique due to multiple ureteral polyps between January 2011 and March 2021 were reviewed at our institute. After administration of anesthesia, patients were placed in a passive position and underwent a three-port transabdominal laparoscopy with RU. Detailed data were reviewed, including demographic characteristics , intraoperative outcomes, and postoperative data, complications, and pathology reports. Results: Thirty-two patients were diagnosed with multiple ureteral polyps underwent this surgery method at our institution. The mean duration of symptoms at the time of diagnosis was approximately 7.1 months. The mean age of patients was 42.4 years, with males accounting for 68.8% (22/32), lesion of left for 56.3 % (18/32), and the upper ureter for 62.5% (20/32). Furthermore, the median length of the polyps was 3.6 cm, mean operative time was 174.6 minutes, and estimated blood loss was about 86.8mL. The mean time to begin a liquid diet and to be out of bed were 1.7 and 2.3 days, respectively. The average length of hospital stay was 6.3 days. The ureteral stent was removed by cystoscope 2 to 3 months after surgery. Follow-up duration ranged from 3 to 112 months and none of the patients required another surgery for recurrence. Conclusion: Transabdominal LAP-UU combined with the intraoperative RU assisted technique is an effective, safe and reliable surgical option for patients with multiple ureteral polyps. Further long-term follow-up is recommended.